Validasi LKPD terintegrasi nilai-nilai karakter dengan learning cycle 5E pada materi fluida kelas XI - Viskia Manelza; Festiyed Festiyed; Yohandri Yohandri; Wahyuni Satria Dewi (PILLAR OF PHYSICS EDUCATION, 2019)
Education is an effort in forming a human character. Strengthened of the government by formulating Presidential Regulation No. 87 of 2017 concerning Strengthening Character Education. But the reality in the field is not in accordance with the expectations that the government wants, this is in accordance with the questionnaire to students at SMAN 1 Batang Anai. It is known that the learning motivation of students is lacking due to the lack of practicum and its support such as student worksheets. Using student worksheets makes the teacher easy to deliver material, so that time becomes more effective. These teaching materials will be used by students during learning, therefore the students’ worksheets can be taken from the worksheet. Therefore, researchers are interested in conducting research by producing products in the form of student worksheets that are integrated character values by using the Learning Cycle 5E model on valid class XI fluid material. This research is a descriptive study using steps to prepare student worksheets according to the Ministry of National Education. This study aims to describe the validity of the student worksheets that have been made. Validation was assessed by three UNP Physics lecturers and one physics teacher at SMAN 1 Batang Anai which were conducted twice. The instrument of data collection used is the instrument validity and the data analysis technique used is descriptive analysis techniques for product validity. Two results were obtained, the results of the first study produced a product in the form of student worksheets that integrated character values with the 5E Learning Cycle model. The results of the second study are the results of the validity test conducted twice, with the average value of the first validity being 84 with very valid criteria and the average value of the second validity is 92 with very valid criteria. So, the conclusion of this study is the integrated worksheet of student values with the 5E Learning Cycle is very feasible to use in learning.